Peningkatan Kompetensi Guru SD dalam Mendesain Pembelajaran Mendalam Berbasis Tatanen di Bale Atikan (TdBA) - Mardiman Mardiman; Nia Fernanda; Agan Syahrial; Eka Yuni Nur Jannah; Putri Ayu Lestari; Novia Dara Puspita; Jeki Purnama Putra; Deni Maulana Suwanta (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to enhance the competence of elementary school teachers in designing deep learning based on the Tatanen di Bale Atikan (TdBA) framework in Purwakarta Regency. The field implementation of TdBA faces challenges regarding teachers' limited competence in integrating local wisdom with a deep learning approach. The study employed Participatory Action Research (PAR) involving 90 educators from six partner elementary schools. The activities were conducted in five stages: needs analysis, workshops, instructional design mentoring, teaching practice based on lesson study, and evaluation. The results indicate an improvement in teachers' conceptual understanding; the average pre-test score rose from 58 (fair category) to 85 (good category) in the post-test, yielding an N-Gain score of 0.57. Teachers successfully integrated the Pancaniti principles and the four TdBA elements into the 180 instructional units produced. The program concludes that the PAR approach is effective in empowering teachers to design holistic learning experiences that foster students' spiritual, social, and ecological awareness. Continuous mentoring through teacher learning communities is recommended to ensure the program's sustainability.